Isolated nonsyndromic cleft palate: multicenter epidemiological study in the Brazil - Samuel Trezena; Renato Assis Machado; Silvia Regina de Almeida Reis; Rafaela Scariot; Ana Lúcia Carrinho Ayroza Rangel; Fabrício Emanuel Soares de Oliveira; Anna Júlia Borges; Alissa Tamara Silva; Daniella R. Barbosa Martelli; Hercílio Martelli Júnior (BMC, 2023)
Abstract Background Nonsyndromic orofacial clefts (NSOC) are the craniofacial most common congenital malformations. There are evidences that the nonsyndromic cleft palate (NSCP) development differs from other NSOC. However, most of the publications treat NSCP without considering that information. Furthermore, few studies focus on NSCP. The aim of this study was to describe epidemiological findings of patients with isolated NSCP in Brazil. Methods In this cross-sectional multicenter study, four reference Centers for treatment in three different Brazilian states was investigated. Data were obtained from clinical records of patients, between November 2021 and June 2022. Researched variables were sociodemographic, clinical characteristics and pregnancy and family history. Pearson's chi-square and ANOVA One-way tests were used for associations. Results Majority were female (58.1%), white (60.7%) with incomplete NSCP (61.2%). There was an association between complete NSCP and a positive history of medical problems during pregnancy (p = 0.016; 27.9%; OR: 1.94; 1.12-3.35). Systemic alterations were perceived in 40.6% of the sample with odds ratio for development of the complete type (OR: 1.21; 0.74-1.97). Higher OR was visualized in medication use during pregnancy (OR: 1.35; 0.76-2.37) and positive family history of oral cleft (OR: 1.44; 0.80-2.55). Dental and surgical care was associated with higher age groups (p < 0.050). Conclusions NSCP was most prevalent in white skin color female. Complete NSCP is associated with medical problems during pregnancy. Medication use during pregnancy and positive family history of oral cleft increase the chance of developing complete NSCP.